PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PT KGS - Salsa Ade Fitria; Heru Sudinta; Temmy Setiawan (IJOSPOL - International Journal of Social, Policy and Law, 2026)
This study aims to analyze the influence of transformational leadership style and work motivation on employee performance at PT KGS. This study used a quantitative approach with a survey method. The research population consisted of 8,885 employees, with a sample size of 90 respondents determined using the Slovin formula at a 10% error margin. Data were collected through a Likert scale questionnaire and analyzed using multiple linear regression. The results of the study indicate that transformational leadership style and work motivation have a positive and significant effect on employee performance, both partially and simultaneously. These findings highlight the crucial role of leaders in providing inspiration, support, and motivation to employees to enhance work productivity. It is recommended that the company strengthen transformational leadership practices and motivation enhancement programs to ensure sustainable development of employee performance.